Beneficial Effects of Ketogenic Diet on Phosphofructokinase Deficiency (Glycogen Storage Disease Type VII) - Similä, Minna E.; Auranen, Mari; Piirilä, Päivi Liisa (Frontiers in Neurology, 2020)
Background A deficiency of muscle phosphofructokinase (PFKM) causes a rare metabolic muscle disease, the Tarui disease (Glycogen storage disease type VII, GSD VII) characterized by exercise intolerance with myalgia due to an inability to use glucose as an energy resource. No medical treatment for GSD VII currently exists. The aim of this study was to determine whether a dietary intervention with excessive fat intake would benefit GSD VII. Patient and methods A ketogenic diet (KD) intervention implemented as a modified Atkins diet was established for one patient with PFKM deficiency with a low late lactate response and very high ammonia levels associated with exercise. We recorded the KD intervention for a total of 5 years with clinical and physiotherapeutic evaluations and regular laboratory parameters. Cardiopulmonary exercise testing, including breath gas analysis and venous lactate and ammonia measurements, was performed before KD and at 3 months, 8 months and 5 years after initiation of KD. Results During the 5 years on KD the patient’s muscle symptoms had alleviated and exercise tolerance had become better. In exercise testing, venous ammonia had normalized, the lactate profile remained similar but oxygen uptake and mechanical efficiency had increased and parameters showing increased ventilation had improved. Conclusions This study is the first to show a long-term effect of KD in GSD VII with an alleviation of muscle symptoms, beneficial effects on breathing, and improvement in exercise performance and oxygen uptake. Based on these findings, KD can be recommended under medical and nutritional supervision for selected patients with GSD VII, although further research of this rare disease is warranted.